IMPLEMENTASI AUGMENTED REALITY DALAM PEMBELAJARAN: DAMPAK PADA GAYA BELAJAR DAN PSIKOLOGIS SISWA - Dortean Amelia Jois Jaha; Pnatmo Welhelmina Masi (Universitas Citra Bangsa, 2026)
This study aims to analyze the impact of Augmented Reality (AR) technology on visual-experiential learning styles and the psychological conditions of high school students in underdeveloped areas. The research was conducted at SMA Fajar Timur Haitimuk using a mixed-method approach with a sequential explanatory design. Quantitative data were collected from 30 twelfth-grade students through questionnaires and analyzed using Pearson correlation and linear regression tests. The results showed a significant positive relationship between learning styles and psychological conditions (r = 0.68, p < 0.05), with learning styles contributing 46.2% to the variation in psychological conditions (R² = 0.462, p < 0.001). Qualitative data were analyzed using Braun and Clarke’s thematic analysis to identify patterns and themes emerging from students’ learning experiences based on interviews with 10 students. The findings revealed that AR enhances motivation, understanding, self-confidence, and learning focus. Students responded positively to the immersive learning experience. In conclusion, AR not only supports cognitive understanding but also improves psychological well-being and is relevant as an innovative learning strategy in secondary education in underdeveloped areas.